A Social Chat Network Site With User Anonymity Consideration (International Journal of Engineering and Computer Science, 2017)
Preserving privacy in social networks against neighborhood attacks is an initiation which uses the definition of privacy called K-anonymity. K-anonymous social network still may leak privacy under the cases of homogeneity and background knowledge attacks. To overcome, we find a place to use a new practical and efficient definition of privacy called G-anonymity. In this paper, we take a step further on preserving privacy in collaborative social network site by developing a site using the G-anonymity to improved user privacy on the social media for unaware and illiterate users. Testing was performed using five users and from the users comment; it was observed that the system is 70% efficient for their usage which is better than the other existing systems.